Culture of Seriola dumerilii - García A.; Díaz M.V. (Marine aquaculture finfish species diversification, 1995)
Seriola dumerilii (Risso 1810) is a marine fish species which is becoming important in aquaculture. Its fast growth rate (reaching 1 kg in the first year), good performance in captivity (acceptance of artificial feeding regime and low mortality) and high commercial value (10-20 ECU/kg) make it a suitable species for intensive farming. Bottle-necks in their culture are reproduction, feeding and pathology. At present, reproduction in captivity have not been successful in the Mediterranean countries. Only a few attempts of artificial fertilization with wild broodstock have produced up to 10 days old larvae. On the contrary, japanese scientists have been successful with the reproduction and larval rearing of S. dumerilii (called 'Kampachi') since 1979 but with most success since 1987. At present, the production of S. dumerilii is mostly based on raising fingerlings captured from the wild. On-growing is generally made in the Mediterranean countries (Spain, Italy) as in Japan on net cages, by using fresh or frozen raw fish as food. More recently, moist pellets are replacing raw fish. S. dumerilii dislike dry pellets, but a newly developed extruded pellet, a so called 'soft-dry pellet', has a high acceptability and palatability for the japanese yellowtail (Seriola quinqueradiata) and potentially for the Mediterranean species. Actually, the current diseases are not so important, except for the 0 plus age class fish where mass mortality sometimes happen to due to a Chlamydia-like epitheliocystis organisms and sanguinicolidae blood flukes. The actual knowledge and techniques about reproduction, larval rearing and on-growing of S. dumerilii in the Mediterranean countries and in Japan, as well as the main problems and prospects in their culture are reviewed in this presentation.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1995/06/14-17, Nicosia (Cyprus)